2006
DOI: 10.1021/tx050358e
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Contribution of P450 3A4 to the Hepatic Carcinogenic Activation of Aflatoxin B1

Abstract: The hepatic carcinogen aflatoxin B1 (AFB1) is metabolized in the liver by at least four different P450s, all of which exhibit large interindividual differences in the expression levels. These differences could affect the individual risk of hepatocellular carcinoma (HCC). We investigated the metabolism of AFB1 in a panel of 13 human liver microsomal preparations using a hepatic abundance model, which takes into account the specific kinetic parameters and the expression levels of these P450s. We found a 12-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 39 publications
(62 reference statements)
3
92
2
4
Order By: Relevance
“…CYP3A4 is mainly expressed in the liver and intestine, and its enzymes are involved in the metabolism of about 50% of all drugs, participating in the metabolic activation and metabolism of several pre-carcinogens (25)(26)(27). Ba et al reported that benzo[a]pyrene, which is metabolized by CYP3A4, promoted HCC metastasis and progression in vitro and in mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP3A4 is mainly expressed in the liver and intestine, and its enzymes are involved in the metabolism of about 50% of all drugs, participating in the metabolic activation and metabolism of several pre-carcinogens (25)(26)(27). Ba et al reported that benzo[a]pyrene, which is metabolized by CYP3A4, promoted HCC metastasis and progression in vitro and in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval for all experimental protocols and study was obtained from the institutional review board at the Shizuoka Cancer Center (Authorization Number: [25][26][27][28][29][30][31][32][33]. Written informed consent was obtained from all patients enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…It may well be that the highest liver cancer areas have a combination of both cancer forming factors plus others such as genetic ones. This certainly is the case for AFB 1 as it has been seen that AFB 1 needs to be activated by the cytochrome P 450 system in particular the CYP 3A4 version plus CYP3A5 and 3A7 (Kamdem et al, 2006). Hence those persons with genetics dictating less expression of these forms of cytochrome P 450 would, in theory, have less chance of developing the cancer and vice versa.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…In Gambia, this mutation was detected in DNA in cases of HCC and was not frequent in the control cases [76][77][78][79]. Transversions G→T or transitions G→A are produced in the third base of codon 249 of the p53 gene and in the first or second base of codon 12 of the H-ras gene [80][81][82][83][84][85]. [86].…”
Section: Oncogenes and Tumour Suppressor Gene P53mentioning
confidence: 99%